ӘЙЙЕМГИ ТҮРКИЙ ӘДЕБИЯТ ҲӘМ ФОЛЬКЛОР БИЛИМДАНЫ (Насимхон Асқарович Раҳмоновтың 70 жыллық юбилейине бағышланады) - Алламбергенов, К.; Алламбергенов, Ҳ. (FAN va JAMIYAT, 2022)
The article analyzes the scientific and creative activity, the scientific school he created, and scientific work of Nasimkhan Askarovich Rahmonov, a scholar of Turkish literature and folklore. The scientist’s theoretical views on literature and folklore, source studies, and linguistics are also mentioned.